Simulation Analysis of Dynamic Load of Synchronous Belt Drive based on MFBD - Cao Zhongliang; Li Shan; Guo Jianhua (Jixie chuandong)
Aiming at the structure features of the trapezoidal tooth synchronous belt and belt pulley,the 3D solid models of synchronous belt and belt pulley are established by using UG,the mesh generation is carried out by using the Hyper Mesh and the models are imported into the multi-body dynamics RecurDyn software,the overall movement dynamic performance analysis of the coupled system dynamics of the trapezoidal tooth synchronous belt is carried out. The influence law of initial tension,spindle speed and drive load changes on the stress of the belt tooth is studied,a new digital simulation analysis method for the synchronous belt design,mechanical characteristic analysis is provided.